2017
DOI: 10.3892/ol.2017.7637
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-α promoter methylation is a biomarker for outcome prediction of cisplatin resistance in triple-negative breast cancer

Abstract: A number of previous studies have indicated the presence of a link between estrogen receptor-α (ERα) methylation and triple-negative breast cancer (TNBC). However, the association between ERα methylation and drug resistance during the treatment of TNBC remains unclear. Methylation-specific polymerase chain reaction was used to investigate the methylation of ERα in the genomic DNA of 35 patients with TNBC who were defined as cisplatin-based chemotherapy-resistant using chemosensitivity testing. Survival probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Shaw et al (23) demonstrated that the level of TMB calculated by total circulating free DNA and the circulating tumor cell count (≥5) were both significantly associated with overall survival in patients with metastatic BC, unlike the cancer-associated biomarkers, including cancer antigen 15-3 and alkaline phosphatase (23,24). The similar trend of estrogen receptor 1 and KRAS proto-oncogene, GTPase gene mutations was absent from primary tumor tissue, and appeared to be acquired with disease progression (23,25). This TMB marker may reflect the degree of metastatic burden and may serve as a favorable predictor for clinical decision-making.…”
Section: Discussionmentioning
confidence: 83%
“…Shaw et al (23) demonstrated that the level of TMB calculated by total circulating free DNA and the circulating tumor cell count (≥5) were both significantly associated with overall survival in patients with metastatic BC, unlike the cancer-associated biomarkers, including cancer antigen 15-3 and alkaline phosphatase (23,24). The similar trend of estrogen receptor 1 and KRAS proto-oncogene, GTPase gene mutations was absent from primary tumor tissue, and appeared to be acquired with disease progression (23,25). This TMB marker may reflect the degree of metastatic burden and may serve as a favorable predictor for clinical decision-making.…”
Section: Discussionmentioning
confidence: 83%
“…Dysregulation of ERα is often associated with advanced breast cancers by altering the ERα-dependent genes that are involved in cell proliferation and metastasis. The loss of ESR1 expression in TNBC is a result of the hypermethylation of specific CpG islands within the ESR1 promoter through regulation of DNA methyltransferase (DNMT) 7,8 . Furthermore, ERα re-expression by 5-aza-dC, a DNMT inhibitor, was shown to inhibit tumor growth of TNBC cells in vitro and in vivo, indicating that its expression can be modulated by epigenetic mechanisms and restore the sensitivity of TNBC to endocrine therapy 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Another relevant issue is the estimation of tumor cell density in tissue samples tested. For example, the percentage of tumor in tissue sections chosen for DNA purification varies widely among published reports, from >30% of tumor cells [ 117 ] to >70% [ 82 , 125 ] or even >90% [ 98 , 122 ]. This variability is very likely to influence the determination of methylation levels (even considering that normalization for input has been made), jeopardizing the comparison of results and the reproducibility of experiments, undermining the possibility of biomarker validation [ 138 ].…”
Section: Discussionmentioning
confidence: 99%